The political business cycle in municipalities in Poland 2001-2019 - Gałązka, Marek (<center>Conference Proceedings Determinants Of Regional Development</center>; No 2 (2021): Conference Proceedings - VIII International Scientific Conference Determinants of Regional Development, 2021)
The aim of the article is to identify the symptom of the political business cycle at the local level in Poland, consisting in increasing budget expenditures during election years in urban, urban-rural and rural municipalities. The article reviews previous empirical studies in foreign and domestic literature. On the basis of data on budgets of local government units in Poland published by the Central Statistical Office for the period 2001-2019, an analysis of the dynamics of total expenditure was carried out and then econometric time series models were estimated using the Cochrane-Orcutte method (autocorrelation correction of the random component). On the basis of calculations of the rate of change of expenditures in the studied period, relatively strong dynamics of expenditures was found in the election years and its significant deceleration in the first years of subsequent terms (with some exceptions). In the models of total, current and property expenditures, apart from the explanatory variable "total income", a zero-one variable was introduced, assuming the value "1" for election years and the value "0" for the remaining years. Thus, the statistical significance of the influence of the election year on the formation of expenditures was measured and weighted independently of the level of total income in municipalities in the cross-section under study. The research hypothesis that there is a significant impulse to increase expenditures in election years in Polish communes and that it is stronger in rural than in urban communes was positively verified. The variable "election year" in the models of total expenditures of rural and urban-rural municipalities turned out to be statistically significant at the level of significance lower than 0.01, while in urban municipalities at the level of significance from 0.01 to 0.05. This means that the impulse to increase expenditures in rural municipalities during the election period is more significant than in urban municipalities. Furthermore, the study found that this symptom relates to property expenditure and not to current expenditure. Thus, this paper has partially filled the research gap regarding the identification of the political business cycle in the cross-section of municipalities into urban, urban-rural and rural.